1997
DOI: 10.1093/ndt/12.5.904
|View full text |Cite
|
Sign up to set email alerts
|

Myofibroblast phenotypes expression in experimental renal scarring

Abstract: Myofibroblasts may play a role in the pathogenesis of glomerulosclerosis, tubulointerstitial fibrosis and vascular sclerosis. Further, the acquisition of new myofibroblastic phenotypes by glomerular and tubular cells may contribute to renal fibrosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
72
0
1

Year Published

1998
1998
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(81 citation statements)
references
References 2 publications
8
72
0
1
Order By: Relevance
“…PCNA is one of the proteins involved in cell proliferation and DNA synthesis, and an increase in PCNA expression is a marker of glomerular sclerosis and tubulointerstitial injury. In addition, the expression of desmin as a marker of podocyte injury [23][24][25] was significantly increased in the vehicle-treated SHR/NDmcr-cp group than in the WKY/Izm group. Previous studies have shown that podocyte damage is an early event leading to glomerulosclerosis and tubulointerstitial damage in Zucker obese rats with type II diabetes mellitus.…”
Section: Discussionmentioning
confidence: 99%
“…PCNA is one of the proteins involved in cell proliferation and DNA synthesis, and an increase in PCNA expression is a marker of glomerular sclerosis and tubulointerstitial injury. In addition, the expression of desmin as a marker of podocyte injury [23][24][25] was significantly increased in the vehicle-treated SHR/NDmcr-cp group than in the WKY/Izm group. Previous studies have shown that podocyte damage is an early event leading to glomerulosclerosis and tubulointerstitial damage in Zucker obese rats with type II diabetes mellitus.…”
Section: Discussionmentioning
confidence: 99%
“…However, although some studies have suggested that markers of renal cell activation and proliferation such as immunostaining of renal biopsies for a-SM-actin and PCNA might be useful diagnostic and/or prognostic indicators in glomerular diseases (3)(4)(5), other studies have shown that these immunohistochemical changes observed during renal disease may be reversible (6)(7)(8).…”
Section: Introductionmentioning
confidence: 99%
“…There is some experimental evidence suggesting that transforming growth factor-ß (TGF-ß) and platelet-derived growth factor (PDGF) can induce phenotypic modifications of these cells (9,10). The a-SM-actin synthesis upregulated by these cells is frequently associated with increased cell proliferation and increased extracellular matrix production (1,5,8,11). PCNA is an acidic nuclear protein whose levels are increased from the late G1 to the S phase of the cell cycle and whose detection parallels other standard methods of assessing cell proliferation such as BrdU labeling and Ki-67 staining (12,13).…”
Section: Introductionmentioning
confidence: 99%
“…It is well known that the cell type responsible for most ECM synthesis is the myofibroblast, distinguished by the acquisition of a α-SMA phenotype. In normal kidney, α-SMA is expressed exclusively in the intrarenal arteries; however, in a number of glomerulonephritis models, mesangial cells are activated into α-SMA positive myofibroblasts and proliferate, producing excessive ECM in glomeruli [3][4][5][6] . In the present study, Western blot analysis showed that α-SMA expression was increased in the renal cortex of nephrectomized rats and that it was decreased with atRA treatment.…”
Section: Wwwchinapharcom Liu X Et Almentioning
confidence: 99%
“…In various types of glomerular injuries, mesangial cells are activated into ECM-producing myofibroblasts that undergo proliferation. These cells are phenotypically defined by their expression of α-smooth muscle actin (α-SMA) [3][4][5][6] . Recently, plasminogen activator inhibitor-1 (PAI-1) has been widely recognized as a key contributor in fibrosis.…”
Section: Introductionmentioning
confidence: 99%